2015
DOI: 10.1161/circresaha.115.307362
|View full text |Cite|
|
Sign up to set email alerts
|

Unique Features of Cortical Bone Stem Cells Associated With Repair of the Injured Heart

Abstract: Rationale: Adoptive transfer of multiple stem cell types has only had modest effects on the structure and function of failing human hearts. Despite increasing the use of stem cell therapies, consensus on the optimal stem cell type is not adequately defined. The modest cardiac repair and functional improvement in patients with cardiac disease warrants identification of a novel stem cell population that possesses properties that induce a more substantial improvement in patients with hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…These early clinical trial results cast doubts as to whether there were any beneficial effects of bone marrow therapy for MI due to fleeting positive impact upon heart function long-term and wide-ranging efficacy [58], prompting a need for additional preclinical studies focused upon these and other stem cell treatment options [59]. One of the recent studies involves swine cortical bone stem cells (CBSCs), demonstrating increased proliferation, migration, cardiac lineage commitment, functional gap junctions and differential response to ATP and histamine stimuli as compared to MSCs or cardiac-derived stem cells [60]. …”
Section: Current Status Of Adult Stem Cell Therapiesmentioning
confidence: 99%
“…These early clinical trial results cast doubts as to whether there were any beneficial effects of bone marrow therapy for MI due to fleeting positive impact upon heart function long-term and wide-ranging efficacy [58], prompting a need for additional preclinical studies focused upon these and other stem cell treatment options [59]. One of the recent studies involves swine cortical bone stem cells (CBSCs), demonstrating increased proliferation, migration, cardiac lineage commitment, functional gap junctions and differential response to ATP and histamine stimuli as compared to MSCs or cardiac-derived stem cells [60]. …”
Section: Current Status Of Adult Stem Cell Therapiesmentioning
confidence: 99%
“…MSC-based therapy, originating from BM-, adipose tissue-, or umbilical cord-cells, continues to gain consent and appeal, because of the large body of preclinical evidence supporting higher paracrine cardioreparative potential 4 . However, poor survival of donated stem cells and failure of stem cell engraftment in the damaged organ occurs within the first days after delivery, posing a significant challenge in the field 1 . A complete understanding of the mechanisms enhancing MSC migration and survival in the microenvironment of the injured myocardium is imperative, to improve both MSC repair capacity and therapeutic application.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction results in compromised myocardial function and heart failure (HF), due to acute and chronic loss of cardiomyocytes 1 . Because adult mammalian hearts have very limited regenerative capacity, stem cell therapy is a potential strategy regenerating myocardium 2 .…”
Section: Introductionmentioning
confidence: 99%
“…We have identified a novel stem cell population, isolated from cortical bone, and have shown that these cells have cardio-protective features, both in vitro 28 and in vivo 29 . Cortical bone stem cells (CBSCs) were found to be distinct from cardiac–derived stem cells (CDCs) and mesenchymal stem cells (MSCs), and they possess characteristics that account for their in vivo cardio–protective features 28 .…”
Section: Introductionmentioning
confidence: 99%